An Analysis of Student's Ability in Using Transition Signals in an Argumentative Essay Written by the Second Semester of English Department Students at Universitas Negeri Padang - Nova Lima Banjarnahor; Don Narius (Universitas Negeri Padang, 2019)
The purpose of this research is to describe the students’ ability in using transition signals in argumentative essay. This research used descriptive qualitative. The population of this research was the second semester of English Department students at Universitas Negeri Padang, Faculty of languages and arts, who registered on 2018 that education program. This research sample is 22 students. Sample were taken using random sampling which students that choose argumentative essay when last term examination. Data were collected by taking from some lectures who teach paragraph writing. Based on the data obtained,the students’ ability in using transition signals in argumentative essay is average (60%)